Naucno-metodiceskoe obosnovanie effektivnosti principov postroenija zašcitnych takticeskich vzaimodejstvij v volejbole - Rodin, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article discusses the analysis and ways to increase protective tactical interactions in modern volleyball. The principles of tactical interaction construction under consideration have been tested under experimental conditions and have shown high efficiency, which allows to recommend them to specialists as key positions determining the result of volleyball player preparation when playing in defense. A determining factor in improving the effectiveness of tactical interactions of volleyballplayers in protection is the emphasis on the application of a specialized training program for players performing the functions of libero (defender).